2010
DOI: 10.1111/j.1439-0310.1979.tb01030.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Organization of African Wild Dogs (Lycaon pictus) on the Serengeti Plains, Tanzania 1967-19781

Abstract: Abstract... African wild dogs were studied ilrcm 1967 ru 1978 or, tile Ser$:ngeti Plains in northern ianzania. The mzin ubjectives werc to dererinine the status ci t1:e sub-population and ro elucidate the eiology and behavior of this social carnivore. Thi: paper describes the decline of the sub-pcpulation, the dynamics of pack composition, and pncterns of dispersal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(65 citation statements)
references
References 13 publications
0
65
0
Order By: Relevance
“…Frequent adult mortalities led to a prevalence of packs with only a single female, with multiple adult females occurring during only about one third of all pack breeding years. This was not surprising given the findings of others (Frame et al 1979;Reich 1981;Creel and Creel 2002) who have noted progressively increasing male bias in older age classes. In the KZN population, generally, males had more contemporaries than females in a breeding pack and, thus, more competitors that decreased the chance of securing dominance after the death of an alpha male.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Frequent adult mortalities led to a prevalence of packs with only a single female, with multiple adult females occurring during only about one third of all pack breeding years. This was not surprising given the findings of others (Frame et al 1979;Reich 1981;Creel and Creel 2002) who have noted progressively increasing male bias in older age classes. In the KZN population, generally, males had more contemporaries than females in a breeding pack and, thus, more competitors that decreased the chance of securing dominance after the death of an alpha male.…”
Section: Discussionmentioning
confidence: 85%
“…The alpha male and female in a given pack were recognized on the basis of: (1) reciprocal male and female scentmarking behavior (Frame et al 1979); (2) obvious co-incidental male and female movement; and (3) mutual offensive and defensive maneuvers in agonistic encounters with other adult pack members (Girman et al 1997). The dominance hierarchy was also inferred from gestures of subordination, including laying the ears flat against the head and/or rotating the head away from a higher ranking individual (van Lawick 1970) as well as passive submission that included a subordinate rolling onto its back in the presence of a more dominant dog (Schenkel 1967).…”
Section: Determining Dominancementioning
confidence: 99%
See 1 more Smart Citation
“…In wild dogs, the sexes play similar roles in hunting, defence, and rearing of offspring Frame et al, 1979;Malcom and Marten, 1982), suggesting that the effect of sex on FCM values is most likely the result of differences in physiology (Tilbrook et al, 2000;Touma and Palme, 2005) rather than behaviour. Interestingly, in contrast to the reports by Creel et al (1997a), we did not find any effect of social status on FCM values in either males or females, as also reported by de Villiers et al (1997).…”
Section: Discussionmentioning
confidence: 99%
“…Reproduction is typically restricted to the dominant pair who maintain their dominance through displays of aggression associated with submission by subordinates (Creel et al, 1997a;Frame et al, 1979). In previous studies, dominant individuals were found to have higher faecal GC concentrations than subordinates throughout the year (Creel et al, 1997a), an observation that was initially counter-intuitive and led to the suggestion that GCs are not mediators of reproductive suppression (Barja et al, 2008;Creel, 2005).…”
Section: Introductionmentioning
confidence: 93%